Development of Quantitative Methylation-Specific Droplet Digital PCR (ddMSP) for Assessment of Natural Tregs - Husseiny, Mohamed I.; Fahmy, Ahmed; Du, Weiting; Gu, Angel; Garcia, Pablo; Ferreri, Kevin; Kandeel, Fouad (Frontiers in Genetics, 2020)
Tregs suppress immune responses in vivo in an antigen-specific manner. Of clinical relevance, Tregs can be isolated and expanded in vitro while maintaining immunoregulatory function. Tregs are classified as CD4+CD25highCD127low FOXP3+ cells. Demethylation of the Treg-specific demethylation region (TSDR) of FOXP3 is found in natural Tregs (nTregs). We report a method for the characterization of the differential methylation pattern of the FOXP3 TSDR in patient-derived and expanded nTregs. Human TSDR sequences from nTregs (unmethylated sequence) and pancreatic (methylated sequence) cells were amplified and cloned into plasmids. A droplet digital TaqMan probe-based qPCR (ddPCR) assay using methylation-specific primers and probes was employed to quantify unmethylated and methylated sequences. The methylation-specific droplet digital PCR (ddMSP) assay was specific and selective for unmethylated DNA in mixtures with methylated DNA in the range of 5000 copies/ µl to less than 1 copy/µl (R2= 0.99) even in the presence of non-selective gDNAs. CD4+CD25highCD127lowFOXP3+ human nTregs, in the presence of Dynabeads or activators, were expanded for 21 days. There was a decrease in the unmethylated ratio of Tregs after expansion with essentially the same ratio at days 10, 14, and 17. However, the activator expanded group showed a significant decrease in unmethylated targets at day 21. The suppression activity of activator-expanded nTregs at day 21 was decreased compared to cells expanded with Dynabeads. These data suggest that the digital droplet MSP-based assay (ddMSP) can quantitatively monitor nTreg expansion in vitro. These data also indicate that the assay is sensitive and specific at differentiating nTregs from other cells and may be useful for rapid screening of nTregs in clinical protocols.